Organization for Safety and Asepsis Procedures (OSAP) - Vickie P. Overman, RDH, MED (Journal compilation 2007 Blackwell Munksgaard, 2007)
The Organization for Safety and Asepsis Procedures (OSAP) is an international, non-profit-making dental organization that promotes safety and infection control.